Superlexical versus lexical prefixes - Romanova, Eugenia (Nordlyd, 2005)
This paper is intended to justify the classification of all the Rus- sian prefixes into lexical and superlexical. It gives semantic and syntactic criteria for distinguishing between the two groups, includ- ing: the idiosyncratic or spatial lexical meaning versus operator-like function; the (in)ability to measure over objects and events; the (in)ability to stack; the (in)ability of a host verb to form secondary imperfective; attaching to (a)telic stems; the (in)ability to change the argument structure of a host verb. Applying these criteria results in finer gradation within the group of superlexical prefixes. It is ac- counted for by their different syntactic positions with respect to vP. At the end of the paper I speculate about the effect this architecture can have on the prefixation of unaccusative and unergative verbs.